2010
DOI: 10.1007/s11243-010-9351-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the ligand substitution reaction of di-μ-hydroxobis(bipyridyl)dipalladium(II) ion with thiourea in aqueous solution

Abstract: The kinetics of the interaction between thiourea and the title complex has been studied spectrophotometrically in aqueous medium as a function of nucleophile concentration, temperature and pH at constant ionic strength. The reaction is a two-step process in which the first step is ligand dependent, but the second step is ligand independent and is assigned to ring closure. The rate and activation parameters, conductivity studies and IR data were used to deduce a plausible mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…S12). Literature reports [61][62][63][64][65][66] indicate that more negative (large) values of DS -is characteristic of an associative substitution mechanism for Pd II and Pt II complexes [67]. The enthalpy of activation (DH -) for both the steps were in fair agreement with those found for related Pd II complexes with subsequent diimine ligands.…”
Section: Kinetic Studysupporting
confidence: 71%
“…S12). Literature reports [61][62][63][64][65][66] indicate that more negative (large) values of DS -is characteristic of an associative substitution mechanism for Pd II and Pt II complexes [67]. The enthalpy of activation (DH -) for both the steps were in fair agreement with those found for related Pd II complexes with subsequent diimine ligands.…”
Section: Kinetic Studysupporting
confidence: 71%
“…With a pK a of 2.0, TU remains in the neutral form from pH ¼ 2 to pH ¼ 10. 27 Therefore, the adsorption of TU on the surface of AuNPs results in signicantly reduced overall surface charges and increased van der Waals attractive force among nanoparticles, promoting the aggregation of AuNPs. In our experiment, it was found that urea, which is structurally similar to TU, could not induce the aggregation of AuNPs, revealing that S atom rather than amino groups of TU plays a key role in the interaction between TU and AuNPs.…”
Section: Construction Of Inhibit Logic Gatementioning
confidence: 99%